2019
DOI: 10.1002/suco.201900160
|View full text |Cite
|
Sign up to set email alerts
|

Punching shear tests of post‐tensioned flat slabs supported on edge columns

Abstract: This paper describes an experimental study of the punching resistance of unbonded post tensioned flat slabs supported on edge columns. Fifteen slabs rectangular in plain, with sides of 2 m by 1.2 m and 120 mm thick were tested, supported on square columns with sides of 200 mm and with length of 600 mm at the top and at the bottom. The main variables are the eccentricity (Mu/Vu) of the shear force, which is obtained varying the relation between loads parallel and perpendicular to the free edge; the amount of un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…In 1990, Foutch et al [5] pointed out the advantages of using PT RC slab solutions according to design strength considerations. Previous research has confirmed that prestressing substantially improves the resistance of flat concrete slabs to punching shear [6][7][8]. From the sustainability perspective, the research conducted by Dane Miller [9] confirmed that by increasing the span length in PT slabs from 6.67 to 13.3 m, the consumption of concrete and steel reinforcement can be decreased by 21.5 and 34.4%, respectively.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…In 1990, Foutch et al [5] pointed out the advantages of using PT RC slab solutions according to design strength considerations. Previous research has confirmed that prestressing substantially improves the resistance of flat concrete slabs to punching shear [6][7][8]. From the sustainability perspective, the research conducted by Dane Miller [9] confirmed that by increasing the span length in PT slabs from 6.67 to 13.3 m, the consumption of concrete and steel reinforcement can be decreased by 21.5 and 34.4%, respectively.…”
Section: Introductionmentioning
confidence: 85%
“…The punching shear strength of flat RC slabs is typically controlled by the compressive strength of the slab and column concrete and their geometric parameters. In a flat slab without shear reinforcement subjected to a cantered axial load by an isolated column, two categories of orthogonal bending moments, M ϕ producing tangential stresses and Mr producing radial stresses, are developed due to the bidirectional flexural action of the slab, as depicted in Figure 18 [6]. The normal stresses, σ ϕ, and σ r , developed by the above-mentioned orthogonal bending moments, respectively, stretch the top and compress the bottom of the slab.…”
Section: Influence Of Prestressing On Punching Strength Of Pt Slabmentioning
confidence: 99%
“…The two-way shear strength of PCS has been experimentally by many researchers (Amir et al, 2016;Barba´n et al, 2019;Burns and Hemakon, 1977;Correa, 2001;Eid, 2013;Franklin and Long, 1982;Gerber and Burns, 1971;Grow and Vanderbilt, 1967;Hasssanzadeh, 1998;Kordina and Nolting, 1984;Koust, 1977;Mao and Yaung, 2012;Melges, 2000;Moreillon, 2008;Mostafaei et al, 2011;Moussa and Salama, 2008;Nylander et al, 1977;Pralong et al, 1979;Ragab et al, 2014;Ramos and Lucio, 2006;Ramos et al, 2008Ramos et al, , 2011Regan, 1983;Rezai Kallage, 1993;Saleh and Suaris, 2009;Scordelis et al, 1958;Shehata, 1982;Silva, 2005;Smith and Burns, 1974). Only two studies focused on PLCS.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, that the twoway shear strength predicted by most international codes is overly conservative. Barba´n et al (2019) tested 15 eccentric slab-column connections, where the slab was rectangle 2 3 1.2 m and 120 mm thickness. The investigated parameters were the loading eccentricity and the flexural reinforcement ratio.…”
Section: Introductionmentioning
confidence: 99%